2020
DOI: 10.1136/gutjnl-2019-319919
|View full text |Cite
|
Sign up to set email alerts
|

Location-specific cell identity rather than exposure to GI microbiota defines many innate immune signalling cascades in the gut epithelium

Abstract: ObjectiveThe epithelial layer of the GI tract is equipped with innate immune receptors to sense invading pathogens. Dysregulation in innate immune signalling pathways is associated with severe inflammatory diseases, but the responsiveness of GI epithelial cells to bacterial stimulation remains unclear.DesignWe generated 42 lines of human and murine organoids from gastric and intestinal segments of both adult and fetal tissues. Genome-wide RNA-seq of the organoids provides an expression atlas of the GI epitheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
99
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(111 citation statements)
references
References 39 publications
11
99
0
1
Order By: Relevance
“…4b, 4G). This compartmentalization of response along the GI tract is consistent with previous reports describing that different sections of the GI tract respond differently to microbial challenges [44]. Most importantly, our results reveal that production of ISGs is mostly restricted to bystander cells, while production of IFN is detected mostly in infected cells (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…4b, 4G). This compartmentalization of response along the GI tract is consistent with previous reports describing that different sections of the GI tract respond differently to microbial challenges [44]. Most importantly, our results reveal that production of ISGs is mostly restricted to bystander cells, while production of IFN is detected mostly in infected cells (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…The low or lack of innate response of human colonoids to IL-1β stimulation is not caused by the ineffectiveness of IL-1β, as IL-1β, even at a concentration of 5 times less, was able to induce higher levels of IL-8 and CCL20 secretion by Caco2 cells (Supp 1F). LPS also failed to induce the secretion of IL-8 and CCL20 by human colonoids, similar to a recent finding 3 (Fig 1B).…”
Section: Human Colonoids Are Highly Responsive To Salmonella Flagellinsupporting
confidence: 91%
“…Since IL-37 typically acts under inflammatory conditions, expression of various innate receptors was evaluated in human colonoids to determine their capacity to respond to pro-inflammatory stimuli. Recently published studies have demonstrated site specific innate receptor expression as well as human specific innate responses by IEC to host or microbial products 2,3,28 . By real-time qPCR analysis, both pediatric and adult colonoids were confirmed to transcribe mRNA for several innate immune receptors including TLR4, TLR5 IL-1R and IL-18R1 (Supp 1B).…”
Section: Pediatric and Adult Colonoids Transcribe Similar Levels Of Imentioning
confidence: 99%
See 2 more Smart Citations